Functional purpose of prohibition to abuse of law in civil code - Dmitriy Aleksandrovich Matantsev, Olga Vyacheslavovna Gridneva,; Stanislavovna Mayorova, Mariia; Leonidovna Burova, Inna; Vladimirovna Timonina, Irina; Aleksandrovna Trofimova, Inessa (Opción, 2019)
This work studies the problem of abuse of civil law, stresses upon the questions of nuisance, circumvention of the law, the use of right that contradicts to its purpose and other related categories. This work uncovers social nature of nuisance as an element of the juridical conflict; analyzes the norms concerning abuse of civil rights, the system and features of specific sanctions concerning the nuisance according to the Civil Code of Russia.